Self-medication practice among pension housed patients at the central healthcare unit of Teresina - Wemíria de Fátima Lima Lopes; Fabrício Ibiapina Tapety; Cintia Maria de Melo Mendes; Maria do Carmo de Carvalho e Martins; Ednaldo Francisco Santos Oliveira Júnior; Tereza Maria Alcântara Neves (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: To investigate the prevalence and characteristics of self-medication among pension housed patients at the central healthcare unit of Teresina in the downtown region. Method: This is an exploratory epidemiological study with a quantitative, cross-sectional descriptive approach. For data collection a semi-structured questionnaire was applied on the behaviors of 300 patients. Results: Of the total respondents, the practice of self-medication was common in 241 (80.33%) of individuals. The greatest achievement of this was seen in those coming from municipalities in the interior of Maranhao 116 (48.13%), which surpassed even that with a small gap the individuals from the interior of Piaui, to practice self-medication in 101 (41.91%). Conclusion: It is understood that self-medication is an old widespread practice. The search for relief from their ailments and the poor public healthcare offered to the population admits that individuals opt for self-medication as a first option.